Worldwide trends of ICT integration in ecology higher education: A bibliometric analysis of Scopus - Muhammad Darwis; L. Lufri; I Made Arnawa; N. Nasirsah; Eka Nurwani Ritonga (JPBI (Jurnal Pendidikan Biologi Indonesia), 2025)
The integration of information and communication technology (ICT) in ecology teaching and learning in higher education is increasingly important to support pedagogical innovation and achieve the Sustainable Development Goals. This study addresses the gap in existing literature, as no comprehensive bibliometric mapping has been conducted to date on ICT integration in ecology learning, despite the growing attention in environmental and digital education. This study maps global trends in ICT integration in ecology learning through a bibliometric analysis of published articles indexed in Scopus. Data was obtained using a structured query filtered by English-language journal articles, final publication stage, and all open access statuses. The search process followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) process. Unlike previous thematic or case-based reviews, this study applies bibliometric techniques to identify knowledge networks, key research clusters, and emerging directions. The analysis used the analyze results menu in Scopus subscriptions, VOSviewer, and Biblioshiny (Bibliometrix-R) to identify general publication characteristics, knowledge maps, and topic trends. The results show Spain, China, and Australia as the leading countries, with ecology, teaching, and learning as dominant keywords. New research themes—particularly digital inclusion and ICT for sustainability—are identified as emerging drivers in the field. These findings emphasize the importance of international collaboration, the application of cutting-edge technology, and pedagogical innovation to achieve the SDGs through learning. Practically, the study provides valuable insights for lecturers, curriculum developers, and policymakers to design ICT-based ecology education that is innovative, inclusive, and aligned with sustainability goals.